Pembuatan Kerajinan Tangan Memayet Baju Adat Dayak di Desa Kutai Lama - Puspita, Meyliya Ayu; Kurniawati, Wiwik Dwi; Azizah, Nor (TAFANI: Jurnal Pengabdian Masyarakat, 2024)
The making of traditional Dayak clothing sequined handicrafts has become an important source of income for UMKM women in Kutai Lama Village. This study aims to analyze the potential of traditional Dayak clothing embroidering handicrafts as a source of opinion in Kutai Lama Village, as well as to evaluate the factors that influence the sustainability and development of this industry. The research methods used are observation, interviews, literature studies and documentation. The sample of this research is UMKM mothers in Kutai Lama Village. The data obtained was analyzed using a qualitative approach. The results of this study showed that the Dayak traditional clothing sequined handicrafts had great potential as a source of income for UMKM women. earn significant additional income, which helps improve their economic well-being. However, the sustainability and development of this industry is influenced by factors such as raw materials, artisan skills.